Dietary polyacetylenes, falcarinol and falcarindiol, isolated from carrots prevents the formation of neoplastic lesions in the colon of azoxymethane-induced rats. Issue 3 (15th February 2017) - Kobaek-Larsen, Morten; El-Houri, Rime B.; Christensen, Lars P.; Al-Najami, Issam; Fretté, Xavier; Baatrup, Gunnar
Abstract : Falcarinol and falcarindiol are found in many food plants of the Apiaceae and are the most important dietary polyacetylenes. Abstract : Falcarinol (FaOH) and falcarindiol (FaDOH) are found in many food plants of the Apiaceae family. Carrots are a major dietary source of these polyacetylenes. Feeding azoxymethane (AOM)-induced rats with carrots and purified FaOH have previously been shown to inhibit neoplastic transformations in the colon. FaOH and FaDOH have also shown to have a synergistic effect in vitro, resulting in a significant increased cytotoxic activity. Based on these findings the antineoplastic effect of FaOH and FaDOH (purity > 99%) was investigated in the AOM-induced rat model. Twenty rats received rat diet containing 7 μg FaOH per g feed and 7 μg FaDOH per g feed and 20 rats were controls receiving only rat diet. Then carcinogenesis was induced in all 40 rats with the carcinogen AOM. All animals received the designated diet for 2 weeks before AOM induction and continued on the designated diet throughout the experiment. Rats were euthanized 18 weeks after the first AOM injection and macroscopic polyp/cancers were measured, harvested and stained for histology. The difference in sizes of aberrant crypt foci (ACF) were analysed in a Wilcoxon rank sum test, in which the median number of small ACF was 218 in controls and 145 in polyacetylene treated rats ( P < 0.001). Fifteen control rats and 8 treated rats had macroscopic tumors ( P = 0.027). The number of tumors larger than 3 mm were 6 and 1 in control and treated rats, respectively ( P = 0.032). In conclusion dietary supplements with FaOH and FaDOH reduced the number of neoplastic lesions as well as the growth rate of the polyps suggesting a preventive effect of FaOH and FaDOH on the development of colorectal cancer.